TELAAH KETELADANAN RASULULLAH SAW DALAM MENDIDIK ANAK MENURUT SYEIKH JAMAL ABDURRAHMAN - Sugeng Tri Siswoyo; Abdul Ghofur (Turats, 2023)
The purpose of this study is to find out how the example of the Prophet Muhammad ineducating children in the Islamic Parenting Book by Sheikh Jamal Abdurrahman. In this study, theauthor uses qualitative research methods with the type of library research, namely collecting datacontained in various library books that refer to the example of the Prophet Muhammad ineducating children as a primary data source and then also supported by various sources. Othersources that are still relevant as secondary data sources. Then in presenting the data, the writeruses descriptive analysis method. The results of this study indicate that according to Sheikh JamalAbdurrahman in his book entitled Islamic Parenting, the example that the Prophet Muhammadtaught in educating children includes several things that parents/educators must know, namely;teaches faith/tawhid, teaches worship, teaches science, guidance and advice, and self-habituation.